A finger-joint based edge connection for the weak direction of CLT plates. (18th July 2022) - Tapia, Cristóbal; Claus, Marian; Aicher, Simon
Abstract: A new connection concept for joining cross-laminated timber (CLT) plates in their secondary direction is presented. The connection consists of two laminated veneer lumber (LVL) gusset plates with finger-joint-like profiles milled on one side which are glued onto the outermost layers of the CLT. It is demonstrated that the joint represents a stiff moment resistant connection, enabling the activation of the normally underutilized biaxiality of CLT plates and expanding the design freedom of architects and engineers. The concept was analyzed by means of analytical and finite element (FE) models for two geometry alternatives, differing in either a 2D or 3D tapered finger profile. The 3D tapered finger profile produced a stress reduction of around 5% in the region of stress concentration and a more even shear stress distribution on the bonded surface. Thereafter, four specimens were manufactured – two of each geometry alternative – and then tested in four- and three-point bending setups in order to assess the behavior at pure bending as well as at combined moment and shear loading, respectively. At pure bending, the studied connection delivered bending capacities of 100% of the characteristic value of the unjointed CLT material. For the case of moment and shear loading, the global capacity was determined by a bending failure in the CLT region subjected to maximum moment, while the joints remained unbroken. Measured deformations and strains during the tests validated the FE model, which can be used to further develop the connection concept, which allows for a full activation of the biaxial behavior of large-span CLT floors. Graphical abstract: Highlights: New LVL-based edge connection for CLT plates in the weak direction. Simulations and experimental results proof a rigid joint behavior. The connection enables full biaxial behavior of jointed CLT plates. Experiments reveal a connection resistance similar to the characteristic CLT plate capacity. The beech LVL gusset plates are profiled with a finger-joint-like pattern. The connection relies on CNC/robotic milling. A gap-filling adhesive was used.